2010
DOI: 10.5551/jat.4051
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Downregulates Akt Signaling and Inhibits Adiponectin Production and Secretion in 3T3-L1 Adipocytes

Abstract: Aim:The aim of this study was to investigate whether environmental endocrine-disrupting chemicals, bisphenol A (BPA) and BPA-related chemicals, affect adiponectin production and secretion in 3T3-L1 adipocytes and whether BPA acts through Akt signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 53 publications
(72 reference statements)
4
40
0
Order By: Relevance
“…However, in the present study, we did not detect any significant changes in Akt phosphorylation in hepatic or adipose tissue after BPA treatment. Another study reported that 24 h of treatment with BPA decreased the level of Akt and Akt phosphorylation in 3T3-L1 adipocytes by 46 and 29% respectively (Kidani et al 2010). In the present study, we also examined the effect of BPA treatment on GSK3b phosphorylation in skeletal muscle and confirmed that BPA decreased GSK3b phosphorylation at Ser9, which thereby increased the activity of GSK3b and insulin resistance.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, in the present study, we did not detect any significant changes in Akt phosphorylation in hepatic or adipose tissue after BPA treatment. Another study reported that 24 h of treatment with BPA decreased the level of Akt and Akt phosphorylation in 3T3-L1 adipocytes by 46 and 29% respectively (Kidani et al 2010). In the present study, we also examined the effect of BPA treatment on GSK3b phosphorylation in skeletal muscle and confirmed that BPA decreased GSK3b phosphorylation at Ser9, which thereby increased the activity of GSK3b and insulin resistance.…”
Section: Discussionsupporting
confidence: 60%
“…Several mechanisms have been proposed to explain the effect of BPA on glucose intolerance, including the disturbance of pancreatic b cell function (Nadal et al 2000, Alonso-Magdalena et al 2006, decreased production or secretion of adiponectin from adipocytes, the establishment of insulin-sensitizing adipocytokine (Hugo et al 2008, Kidani et al 2010, enhanced adipocyte differentiation and lipid accumulation (Masuno et al 2002, 2005, Somm et al 2009, Ohlstein et al 2014, and increased insulin resistance resulting from increased oxidative stress and mitochondrial dysfunction (Nakagawa & Tayama 2000, Bindhumol et al 2003, Asahi et al 2010, Moon et al 2012.…”
mentioning
confidence: 99%
“…For instance, BPA treatment diminished adiponectin production in 3T3-L1 adipocytes. 162 Long-term exposure of DDT caused a reduction of serum RBP4 levels, leading to an inadequate intake of vitamin A, 163 which is an important factor for the regulation of spermatogenesis. 164 Intriguingly using retinoic acid (RA) reporter assay, PFOS was found to inhibit RA-mediated transactivation of retinoic acid response element (RARE) (unpublished data , Fig.…”
Section: Effects Of Edc On Adult Spermatogenesismentioning
confidence: 99%
“…92 Other in vitro and in vivo studies performed in both laboratory animals and humans showed BPA at environmentally relevant doses to reduce the secretion of adiponectin, 93 a hormone produced by adipose tissue that can protect an individual from diabetes, by inhibiting the activation of protein kinase B (PKB, also known as AKT, a downstream regulator of the PI3K signaling pathway). 56 PKBβ/Akt2 null mice also displayed insulin resistance with animals developing β-cell failure and diabetes, [94][95][96] illustrating that BPA targets an important regulator of human physiology. It remains to be determined if BPA also interferes with the production of leptin, a protein that controls body weight, metabolism and reproductive function.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Conversely, adults with the highest levels of circulating BPA were more than twice orphan seven-transmembrane spanning receptor that is structurally different from ER 50,51 ) with high affinity, resulting in the production of cAMP and in the activation of alternative estrogen signaling cascades [e.g., extracellular-regulated kinases 1 and 2 (ERK1/2) and phosphoinositide-3-kinase (PI3K)], that is, via non-genomic pathways that are outside of the classical ER pathway. [51][52][53][54][55][56] Inappropriate MAPK activation such as that initiated by the binding of BPA to GPR30 may also lead to a variety of human cancers 57 because estrogens and xenoestrogens can increase cell proliferation directly or indirectly via growth factors, and this can favor tumorigenesis. 58,59 In addition, BPA binds estrogen-related receptor γ (ERRγ, an orphan nuclear receptor that does not directly bind estradiol 17β) 60,61 and aryl hydrocarbon receptor (AhR, a transcription factor that plays an important role in xenobiotic metabolism), 62 illustrating that BPA has many cellular targets.…”
Section: Environmental Toxicants Metabolic Diseases and Male Reprodumentioning
confidence: 99%